Ortak Girişim Stratejisi ile Global Pazarlara Giriş - DENİZ, RECEP BAKİ (Marmara Üniversitesi, 2002)
There is no denying that international markets present a challenging and steadily growing opportunity for global expansion of the business base. One of the most significant developments in business practice in recent years has been the raped growth of international activities. The major considerations associated with entry into foreign locations are: direct exporting, indirect exporting, Licence, franchising, joint ventures and direct investment. This paper covers joint venture strategy with its advantages and disadvantages, in addition to emphasizing the factors for making a joint venture successful.
Keywords: Ortak Girişim Stratejisi; Global Pazar